Analisis simbol pada antologi puisi singkawang karya pradono (kajian semiotika) - Fitri Wulansari; Muhammad Rifa’i; Elva Sulastriana (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
This research generally aims to describe signs in the form of symbols, with the study of semiotics in Poetry Anthology Singkawang by Pradono, then clearly reveals the use of symbols in it. The method used is a descriptive method with a qualitative research form. The source of data in this study is the book Anthology of Singkawang Poetry by Pradono. The approach used is a semiotic approach. The technique used in data collection is a documentary study technique, and the instrument in this research is the researcher himself. Based on the relationship between the sign and the signified in the anthology of Singkawang poetry by Pradono, it has a sign system in the form of symbols, then the study of semotics can deepen the ability to understand poetry interpretation and deepen the teaching of the sign system contained in a literary work., Village